Pengembangan Model Project Based Learning (PjBL) Berbasis Etno STEM dalam meningkatkan Literasi Numerasi Siswa di Sekolah Dasar - Dewi Sartika; Mikrayanti Mikrayanti; Alimudin Alimudin; Afan Julkarnain (FKIP Universitas Mataram, 2025)
The low level of numeracy literacy among students in the city of Bima and West Nusa Tenggara requires more contextual and relevant learning innovations that are relevant to local life and culture. This study aims to develop an Project Based Learning (PjBL) based ethno-STEM to improve the numeracy literacy of elementary school students. The research method used a research and development approach, which included needs analysis, model design, expert validation, limited trials, and effectiveness testing at SDN 11 Kota Bima. Data collection instruments consisted of questionnaires, observation sheets, and numeracy literacy tests. The validity test results showed that the Project Based Learning (PjBL) based ethno-STEM met the criteria for content, language, and implementation feasibility. The application of the model in field trials provided a significant improvement in students' numeracy literacy skills compared to conventional learning, as indicated by higher post-test scores and positive responses from teachers and students. These findings confirm that the integration of local culture in project-based learning effectively improves students' understanding of mathematical concepts and problem-solving skills. This study concludes that the Project Based Learning (PjBL) based ethno-STEM can be an alternative contextual and relevant learning innovation to improve numeracy literacy in elementary schools